Empirical Evaluation of Grid Computing Emerged Resource Scheduling Algorithms - E., Chandra Blessie; P., Pradeep Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Grid computing is a group of computers that are physically connected over a network or the Internet to perform dedicated tasks together, such as analyzing e-commerce data, solving complex problems, and many other complicated jobs. Previously, many industries and additionally, research institutions are working in this emerging sector to overcome the existing issues and are also in process of enhancing the existing working methods to get better performances. In this paper, the authors suggested an enhanced model in the resource scheduling algorithm to enhance the performance of some existing methods. In the comparison segment, it shows that the proposed model provided better results than some existing models. The grid computing must be enhanced with a certain limit of interval to maintain the performances that are required for the real-time scenarios.